Treatment of Intracranial Aneurysms with the Pipeline Embolization Device Only: a Single Center Experience - Maus Volker; Mpotsaris Anastasios; Borggrefe Jan; Abdullayev Nuran; Liebig Thomas; Dorn Franziska; Stavrinou Pantelis; Chang De-Hua; Kabbasch Christoph (Neurointervention, 2018)
PurposeThe aim of this study was to evaluate the technical feasibility and rate of mid-term occlusion in aneurysms treated solely with the Pipeline Embolization Device (PED) in a German tertiary care university hospital.Materials and MethodsForty-nine non-consecutive intracranial aneurysms underwent endovascular treatment using the PED exclusively between March 2011 and May 2017 at our institution. Primary endpoint was a favorable aneurysm occlusion defined as OKM C1-3 and D (O'Kelly Marotta Scale). Secondary endpoints were retreatment rate and delayed complications. Median follow-up was 200 days.ResultsThe mean aneurysm size was 7.1 ± 5.3 mm. Forty-four aneurysms were located in the anterior circulation (90%). Ten aneurysms were ruptured (20%). Branching vessels from the sac were observed in 11 aneurysms (22%). Favorable obliteration immediately after PED placement was seen in 13/49 aneurysms (27%), of those nine aneurysms were completely occluded (18%). Angiographic and clinical follow-up was available for 45 cases (92%); 36/45 aneurysms (80%) were occluded completely and 40/45 aneurysms (89%) showed a favorable occlusion result. A branching vessel arising from the aneurysm sac was associated with incomplete occlusion (P < .05). All electively treated patients had good outcome (mRS 0). Three aneurysms (6%) required additional treatment due to aneurysm recurrence.ConclusionIn our series, treatment of intracranial aneurysms with the PED was associated with favorable occlusion rates and low complication rates at mid-term follow-up. The presence of branching vessels arising from the aneurysms sac was predictive for an incomplete occlusion.